Orchestral role of lipid metabolic reprogramming in T-cell malignancy - Mehta, Arundhati; Ratre, Yashwant Kumar; Soni, Vivek Kumar; Shukla, Dhananjay; Sonkar, Subhash C.; Kumar, Ajay; Vishvakarma, Naveen Kumar (Frontiers in Oncology, 2023)
The immune function of normal T cells partially depends on the maneuvring of lipid metabolism through various stages and subsets. Interestingly, T cell malignancies also reprogram their lipid metabolism to fulfil bioenergetic demand for rapid division. The rewiring of lipid metabolism in T cell malignancies not only provides survival benefits but also contributes to their stemness, invasion, metastasis, and angiogenesis. Owing to distinctive lipid metabolic programming in T cell cancer, quantitative, qualitative, and spatial enrichment of specific lipid molecules occur. The formation of lipid rafts rich in cholesterol confers physical strength and sustains survival signals. The accumulation of lipids through de novo synthesis and uptake of free lipids contribute to the bioenergetic reserve required for robust demand during migration, and metastasis. Lipid storage in cells leads to the formation of specialized structures known as lipid droplets. The inimitable changes in Fatty acid synthesis (FAS) and Fatty acid oxidation (FAO) are in dynamic balance in T cell malignancies. FAO fuels the molecular pumps causing chemoresistance while FAS offers structural and signalling lipids for rapid division. Lipid metabolism in T cell cancer provides molecules having immunosuppressive abilities. Moreover, the distinctive composition of membrane lipids has implications for immune evasion by malignant cells of T cell origin. Lipid droplets and lipid rafts are contributors to maintaining Hallmarks of Cancer in malignancies of T cells. In preclinical settings, molecular targeting of lipid metabolism in T cell cancer potentiates the antitumor immunity and chemotherapeutic response. Thus, the direct and adjunct benefit of lipid metabolic targeting is expected to improve the clinical management of T cell malignancies.